Determinants of Industrial Performance in the EU-15 Countries, 1980-2003 - George Petrakos; Dimitrios Kallioras; Ageliki Anagnostou (European Regional Science Association (ERSA), 2006)
The process of EU integration has been associated with a variety of outcomes in time and space. A critical question has to do with the impact of open markets on the differences, in economic performance, among more and less advanced countries. Given that industrial activity is more exposed to the forces of integration than any other productive activity, this discussion is more interesting when it focuses on industry. The paper aims to detect the determinants of industrial performance in the EU-15 countries covering the period 1980-2003 in the ongoing process of EU integration. Understanding the factors behind success and failure may have an added value for policy-making at a time when EU structural and cohesion policies are under scrutiny.
Keywords: 330